Strategi Komunikasi Pemasaran Dinas Kebudayaan dan Pariwisata Kabupaten Karo dalam Pengembangan Pariwisata Berastagi - Sinaga, Andika Ariyoga; Khairullah, Khairullah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Berastagi tourism has great potential in supporting Karo Regency's economic growth, but competition with other destinations demands an effective marketing communication strategy. This study analyzes the strategy implemented by the Karo Regency Culture and Tourism Office in the development of Berastagi tourism. Using a qualitative approach with the case study method, data was collected through interviews, observations, and documentation studies, and then analyzed with thematic analysis. The results of the study show that marketing communication strategies include digital promotion, cooperation with stakeholders, organizing cultural events, and strengthening destination branding.  Digital promotion is effective in increasing Berastagi tourism exposure, but it is constrained by budget and experts. Cooperation with travel agents and local communities has had a positive impact, but coordination still needs to be improved. Cultural festivals attract tourists, but promotion is still not optimal. Destination branding is not well structured and needs to be strengthened to be more competitive in North Sumatra. This research recommends increasing digital marketing, optimizing cultural promotion, and more innovative branding strategies so that Berastagi is more competitive as a leading tourist destination in North Sumatra.